Maternal anaemia and its effects on neonatal anthropometric parameters in patients attending a tertiary care institute of Solan, Himachal Pradesh, India - Behal, Manisha; Vinayak, Rajeev; Sharma, Anuj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Anaemia during pregnancy is a significant concern in India. The consequences of iron deficiency anaemia during pregnancy are often serious and long lasting for both the mother and the foetus. Haematocrit measurement is an acceptable and recommended method for anaemia determination especially in situations where limited resources are available, and the technical support is poor. There is a rough conversion factor of 3 which converts the HCT value to approximate haemoglobin level. Present study desires to know the prevalence of anaemia (with classification into mild, moderate and severe) in 3rd trimester pregnancy, to know effect of anaemia in pregnancy on new-born anthropometric parameters and to assess the validity of the threefold conversion between haemoglobin and haematocrit for the determination of anaemia in pregnancy. Methods: The estimation of haematocrit was done by micro-haematocrit method and estimation of haemoglobin was done by automated blood cell analyzer based on cyanmethemoglobin method. Welch's ANOVA, Post Hoc games Howell test and Bland Altman limits of agreement method were used for statistical analysis. Results: Present study showed that 53.75% women in their 3rd trimester were anaemic (mild, moderate and severe anaemic mothers were 22.25%, 28.25% and 3.25% respectively). The standard 3-fold conversion between the haemoglobin and haematocrit was not found to be valid for the assessment of anaemia in the 3rd trimester pregnancy. Finally, while comparing anthropometric measurements between mild/ no anaemia group with severe anaemia group we found that all measurements were less in severe anaemia group and this difference was statistically significant. Conclusions: This study shows that 53.75% women in their 3rd trimester were anaemic, which closely mimic the WHO data but is about 11% more than the prevalence in Himachal Pradesh. Secondly, the standard 3-fold conversion between the haemoglobin and haematocrit was not found to be valid for the assessment of anaemia in the 3rd trimester pregnancy. Finally, birth weight, height, head circumference, chest circumference and mid-arm circumference were significantly affected by third trimester haemoglobin that too the most in severe anaemia cases.